Evaluation of Cyto - and Genotoxic Influence of Lanthanum Dioxide Nanoparticles on Human Liver Cells - Saba M. Alsubaie; Daoud Ali; Bader O. Almutairi; Rafa Almeer; Saud Alarifi (SAGE Publishing, 2022)
Inorganic nanoparticles are representing an emerging paradigm in molecular imaging probe design. We have determined lanthanum oxide nanoparticles (La 2 O 3 NPs)-induced toxicity on human livers cells for 48 hrs. Before exposure to La 2 O 3 NPs, the size and shape of NPs were confirmed by transmission electron microscope. It was found at 32 ±1.6 nm with a sheet-like morphological structure. The viability of CHANG and HuH-7 cells was reduced as the concentration of La 2 O 3 NPs increased. HuH-7 cells were more sensitive than CHANG cells to La 2 O 3 NPs. We observed production of intracellular ROS in HuH-7 cells was more than CHANG cells and the LPO level was more in CHANG cells than in HuH-7 cells at 50 μg/ml of La 2 O 3 NPs. Glutathione was decreased and catalase was increased at 50 μg/ml of La 2 O 3 NPs. More apoptotic and necrotic cells were observed at 300 μg/ml in HuH-7 cells FACS. DNA damage was observed by the SGCE test and more DNA damage was found in CHANG cells than HuH-7 cells at 300 μg/ml La 2 O 3 NPs over 48 hrs. Thus, study warrants the application of La 2 O 3 NPs in daily life and provides vital information about the toxicity of La 2 O 3 NPs.